PEMBELAJARAN MATEMATIKA DENGAN MODEL KOOPERATIF TIPE JIGSAW UNTUK MEMBINA KARAKTER TANGGUNG JAWAB SISWA - Arbainah Arbainah (FKIP ULM, 2019)
Abstract: This study aims to determine the effectiveness of the application of the jigsaw type of cooperative learning model to train the character of responsibility and improving student mathematics learning outcomes. This research type is quasi experiment with One-Group Times Series Design. The research subjects were 30 eighth grade Junior High School (SMP) students. Research data collection was carried out through tests and observations. The results of the study showed: (1) the character of student responsibility which “became a habit” of 16.67%; “had developed” by 20.00%; and “began to grow” by 63.33%, (2) the average score of student learning outcomes in the final test was 80.00 with good qualifications. Keywords: Responsibility character, jigsaw Abstrak: Penelitian ini bertujuan untuk mengetahui efektivitas penerapan model pembelajaran kooperatif tipe jigsaw dalam membina karakter tanggung jawab dan meningkatkan hasil belajar matematika siswa. Jenis Penelitian ini adalah quasi eksperiment dengan One-Group Times Series Desain. Subjek penelitian merupakan siswa kelas VIII SMP yang berjumlah 30 orang. Pengumpulan data penelitian dilaksanakan melalui tes dan observasi. Hasil penelitian menunjukkan: (1) karakter tanggung jawab siswa yang ”menjadi kebiasaaan” sebesar 16,67%; ”sudah berkembang” sebesar 20,00%, dan ”mulai berkembang” sebesar 63,33%, (2) skor rata-rata hasil belajar siswa pada tes akhir sebesar 80,00 dengan kualifikasi baik. Kata kunci: karakter tanggung jawab, jigsaw